The impact of olfactory dysfunction on interoceptive awareness - Krajnik, Jacqueline; Kollndorfer, Kathrin; Notter, Lisbeth A.; Mueller, Christian A.; Schöpf, Veronika (Psychophysiology, 2015)
This study aimed to investigate how the impairment of the olfactory system influences interoception. Interoception is known as the awareness of one's body or the sense of the condition of the body; more precisely, this construct is defined as the processing, representation, and perception of the internal physical state. Interoceptive sensitivity and chemosensory performance were assessed in 77 subjects, including 43 functional anosmics, 18 hyposmics, and 16 healthy controls. Interoceptive awareness was predicted by odor detection threshold, as well as the duration of olfactory loss in patients who suffered from reduced olfactory function—the longer the olfactory impairment, the worse the perception of bodily signals. The results of this study will significantly contribute to the basic understanding of the multifaceted effects of olfactory alterations.